Democracy and International Trade: Differential Effects from a Panel Quantile Regression Framework - Astrid Krenz; Ana Abeliansky (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
There has been a wide debate on whether democracy actually has an effect on economic outcomes, and especially on international trade. In reality, economies very active in the international trading network are not necessarily the most democratic countries. With a new estimation strategy, we analyze this relationship taking a look at the distribution of countries' trading activity. Using a panel quantile estimation framework, we find a stronger relationship at the lower quantiles, especially for the import activity. Our results suggest that the impact of democratization on trade is more important when countries trade less: the marginal benefit of democratization decreases as countries trade more. The results are robust to different institutional variables and even to instrumental variables estimation. Our results demonstrate that the effect of democracy on trade is underestimated using Ordinary Least Squares estimation for the group of countries for which the effect is statistically significant for, namely those countries that are active in the lower quantiles of the trading distribution.
Keywords: F14; F63; C21; 330